Pengaruh Etos Kerja, Hubungan Kerja Dan Lingkungan Kerja Terhadap Motivasi Guru Yang Dampaknya Pada Kinerja Guru: (Studi Kasus Komunitas Mgmp Kimia Sma Negeri Jakarta Timur 1) - Mei Wanita Simanjuntak; Rudianto Rudianto; Jones Zenas Rante; Marisi Pakpahan (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the influence of work ethic, work relationships, and work environment on work motivation and its impact on teacher performance at SMA Negeri Jakarta Timur 1. A quantitative approach was employed, with data collected through questionnaires and analyzed statistically. The results indicate that the implementation of work ethic, work relationships, and work environment at the school received very positive evaluations from the teachers. Work ethic and work environment were found to have a significant direct effect on work motivation, while work relationships did not show a direct effect on motivation. On the other hand, work ethic and work relationships had a direct impact on teacher performance, whereas the work environment did not show a direct influence on performance. Teacher work motivation also proved to significantly affect performance improvement. These findings highlight the importance of strengthening work ethic and the quality of work relationships in enhancing teacher motivation and performance within educational settings.